Practicing Social Research : guied activities to accompany. - Babbie, Earl R.; Huitt, Robert E. (Belmont, California US: Wadsworth Publishing Company, 1979)
CIENCIAS SOCIALES
Keywords: CIENCIAS SOCIALES; INVESTIGACION SOCIAL; MANUALES